(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Employee engagement has long been recognized as one of the most crucial issues in the company. Organizations prioritize maintaining individuals with the skills and competencies required for development and sustainability while also energizing their workforce. Organizational communication and management techniques are only two aspects that impact the diverse idea of engagement. A manager's talent to keep workers motivated is emotional intelligence, which allows a leader to comprehend his and his team members' sentiments. Emotional intelligence refers to adaptive emotional functioning, including associated skills for perceiving, understanding, using, and emotion management among oneself and others. Researchers from various disciplines have examined emotional intelligence and discovered that the concept is linked to several things, including mental health, relationship happiness, and job success. The goal of the current study is to determine how employee emotional intelligence affects managers' emotional maturity and employee engagement. Sample of 196 respondents were surveyed to know the role and impact of emotional intelligence in employee engagement. It is found in the study that EI plays a significant role in employee engagement.